Pemberdayaan UMKM Melalui Sinergi Praktik Ramah Lingkungan dan Pemasaran Digital pada Usaha Warung Makan Mbokcentil - Santi Rimadias; Dikdik S. Sadikin; Raden Bambang Budhijana; Ferenisyah Ardianto; Muhammad Fikri Azmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
In an effort to improve the performance and competitiveness of Micro, Small and Medium Enterprises (MSMEs), the synergy of environmentally friendly practices with digital marketing is an important focus. The community service carried out highlights Warung Makan Mbokcentil, an MSME that is not yet accustomed to environmentally friendly practices and is less than optimal in digital marketing strategies. Through community service initiatives, efforts are being made to promote environmentally conscious practices, recommending the implementation of packaging made from cassava leaves—commonly known as cassava bags, as a more environmentally friendly way of doing business at Warung Makan Mbokcentil. At the same time, community service activities strengthen digital marketing efforts by introducing barcode scanning for complaint services. This innovation facilitates fast and efficient customer feedback, thereby driving continuous improvement in the quality of Warung Makan Mbokcentil's services. In addition, strategic use of social media across related platforms is used to expand market reach and strengthen customer engagement. This community service activity uses interview, observation and mentoring methods. The results of the service underline the positive impact of the synergy of environmentally friendly practices and digital marketing at Warung Makan Mbokcentil. This collaborative approach makes a significant contribution to increasing operational efficiency, enhancing brand image and supporting environmental sustainability. Additionally, it has proven to play an important role in expanding market share through increasing presence on social media platforms.